Wpływ koncepcji Maurice’a Hauriou oraz Santiego Romano na instytucjonalizm w myśli Carla Schmitta - Wyspiański, Bartosz (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2024)
The author starts by describing decisionistic theory of Carl Schmitt. He alleges among other two main interpretations of this doctrine and then characterizes his conception of commissarial and sovereign dictatorship. Afterwards the author depicts critical reflections of Schmitt’s decisionism presented by Karl Löwith and Leo Strauss. In the next part of article, he introduces the doctrine of institutionalism and briefly portrays two of it’s main thinkers – Maurice Hauriou and Santi Romano. After that the author presents their theories more extensively. Ultimately, he points out influence both French and Italian jurists had on institutional theory presented by Carl Schmitt. Especially putting emphasis on similarities and differences between those doctrines.
Keywords: Schmitt, Carl (1888-1985); instytucjonalizm; pozytywizm; decyzjonizm